2016
DOI: 10.1016/j.kint.2016.03.035
|View full text |Cite
|
Sign up to set email alerts
|

An NLRP3-specific inflammasome inhibitor attenuates crystal-induced kidney fibrosis in mice

Abstract: Intrarenal crystal formation activates the Nlrp3 inflammasome in myeloid cells and triggers a profound inflammatory response. Here, we studied whether a specific inhibitor of the Nlrp3 inflammasome, CP-456,773, can prevent kidney fibrosis in a murine model of crystal nephropathy induced by diets rich in oxalate or adenine. Inflammasome activation in renal dendritic cells and the resulting interleukin (IL)-1β and IL-18 production were markedly reduced by CP-456,773 treatment both ex vivo and in vivo. We directl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
111
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(117 citation statements)
references
References 56 publications
5
111
0
Order By: Relevance
“…In addition, Vilaysane et al showed that activation of the Nlrp3 inflammasome is involved in UUO-induced renal inflammation and leads to renal fibrosis [26]. Recently, it was also demonstrated that an Nlrp3-specific inflammasome inhibitor significantly improved crystal-induced renal inflammation and fibrosis [27]. We previously showed that mtROS-mediated Nlrp3 inflammasome activation directly contributed to Aldo-induced renal injury in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…In addition, Vilaysane et al showed that activation of the Nlrp3 inflammasome is involved in UUO-induced renal inflammation and leads to renal fibrosis [26]. Recently, it was also demonstrated that an Nlrp3-specific inflammasome inhibitor significantly improved crystal-induced renal inflammation and fibrosis [27]. We previously showed that mtROS-mediated Nlrp3 inflammasome activation directly contributed to Aldo-induced renal injury in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…Deficiency of inflammasome components, NLRP3, and ASC in mice reduced renal inflammation during progressive renal failure in nephrocal­cinosis-related CKD [39, 40]. Furthermore, chemical inhibition of NLRP3 using a specific inhibitor – CP-456773 or β-hydroxybutyrate – reduced renal inflammation and progressive decline in renal function in murine nephrocalcinosis-related CKD [40, 41]. Inflammasome activation leads to secretion of mature IL-1β and IL-18 that contribute to renal inflammation.…”
Section: Type 2 Crystalline Nephropathy: Intratubular Crystal Formationmentioning
confidence: 99%
“…Inflammasome activation leads to secretion of mature IL-1β and IL-18 that contribute to renal inflammation. Surprisingly, IL-1 receptor inhibition using anakinra has no effect on progressive decline in renal function in murine nephrocalcinosis-related CKD [40, 41], suggesting a contribution of inflammasome-independent functions of NLRP3, which involve transforming growth factor beta receptor signaling-mediated renal fibrosis [42]. Indeed, chemical inhibition of NLRP3 by CP-456773 during oxalate and adenine nephropathy or by β-hydroxybutyrate during oxalate nephropathy reduced intrarenal fibrosis in murine crystalline CKD models [40, 41].…”
Section: Type 2 Crystalline Nephropathy: Intratubular Crystal Formationmentioning
confidence: 99%
“…In most of these studies, the amount of T-cells in the renal interstitium correlates positively with the progression of albuminuria, creatinine retention, and renal structural damage, as shown in Table 1 [36][37][38][39][40][41][42][43]. Corroborating these findings, a number of experimental studies showing significant evidence that anti-inflammatory treatment, as well as the knockout (KO) of specific pro-inflammatory genes can be effective to detain the evolution of nephropathy in different animal models of CKD, have been recently published, as shown in Table 2 [44][45][46][47][48][49][50][51][52].…”
Section: Overview Of Ckd Pathophysiologymentioning
confidence: 90%